IMPACT OF TILLAGE AND SOIL MANAGEMENT ON POPULATION DENSITY AND BIOMASS OF A MEGASCALECID EARTHWORM LAMPITO MAURITII - MRIDULA KUMARI; M. P. SINHA (The Bioscan, 2012)
Agricultural practices can affect earthworms directly by the mechanical action of the tillage operation as well as indirectly as a result of the consequent change in the soil and environment. The effect of tillage practices on earthworm population used as an indicator of soil biological status, has been studied by comparing the population of a no-tilled area to that of a tilled area. A marked difference in population density, age structure and biomass of earthworms, between the tilled land and the no- tilled land has been observed. Results showed that maximum population density of the earthworm Lampito mauritii was 560±28.09 worms m-3 in the no-tilled area, where as in the tilled area density was 540±23.09 worms m-3, with a difference in total worm density by 16%. In the no- tilled area immatures, matures and juveniles contributed 61.35, 24.9 and 13.75 percent respectively (on annual average basis) to the total population, where as in the tilled area percent contribution was 73.40, 13.54 and 13.06 of immatures, matures and juveniles respectively. The immature was 12.05% higher in the no-tilled plot to that of the tilled plot. The paper deals in detail with the impact of agricultural practices on the dominant earthworm species (L. mauritii) found in both grassland and cropland.